PHILOSOPHICAL ANALYSIS OF THE MECHANISMS OF SOCIAL INTERACTION IN UPGRADING THE CULTURE OF LEGAL LITERACY - Kenjayev Burgutali Koviljon ugli (Bright Mind Publishing, 2025)
The article analyzes the role and significance of social cooperation mechanisms in the process of raising the culture of legal literacy in the society of New Uzbekistan from a socio-philosophical point of view. Legal literacy is interpreted as a process related not only to knowledge of normative legal acts, but also to a person's conscious attitude to rights and freedoms, acceptance of legal values as an internal need.